Tuhan dalam Pergulatan Pemikiran Soekarno - Syarifuddin Syarifuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
The tendency for a godless human nature as beings created by god.  Sukarno in his capacity as a president of the Republic of Indonesia, as well as a  thinker and politician, participated gave an interesting discourse on the idea of  god. God on Sukarno opinions is not only have twenty kinds of characteristic, but  not infinite, the qur'an as a Muslims guide, when read, internalized, and kept in  mind, in Sukarno opinions qur’an was enlighted humans to understand and  appreciate the existence of god itself. In Sukarno opinions qur’an was  revolutionized the human mind, brought a revolution in the view of qur’an can  provide an answer the human mind. Sukarno also gave the idea of theological  matters was very interesting to observe. Therefore, thinking of god in Soekarno  belief different with other Muslims. In Sukarno opinions, god has infinite nature,  god remains supreme, not spelled out. Sukarno life is not colored by islamic life,  but his adult life has been a follower of Islam. To be a moeslim, Soekarno has  traveled a long odyssey of the mind, tireless in his search for truth The tendency for a godless human nature as beings created by god.  Sukarno in his capacity as a president of the Republic of Indonesia, as well as a  thinker and politician, participated gave an interesting discourse on the idea of  god. God on Sukarno opinions is not only have twenty kinds of characteristic, but  not infinite, the qur'an as a Muslims guide, when read, internalized, and kept in  mind, in Sukarno opinions qur’an was enlighted humans to understand and  appreciate the existence of god itself. In Sukarno opinions qur’an was  revolutionized the human mind, brought a revolution in the view of qur’an can  provide an answer the human mind. Sukarno also gave the idea of theological  matters was very interesting to observe. Therefore, thinking of god in Soekarno  belief different with other Muslims. In Sukarno opinions, god has infinite nature,  god remains supreme, not spelled out. Sukarno life is not colored by islamic life,  but his adult life has been a follower of Islam. To be a moeslim, Soekarno has  traveled a long odyssey of the mind, tireless in his search for truth